2015
DOI: 10.1080/07370024.2015.1085310
|View full text |Cite
|
Sign up to set email alerts
|

Go-with-the-Flow: Tracking, Analysis and Sonification of Movement and Breathing to Build Confidence in Activity Despite Chronic Pain

Abstract: Chronic (persistent) pain (CP) affects 1 in 10 adults; clinical resources are insufficient, and anxiety about activity restricts lives. Technological aids monitor activity but lack necessary psychological support. This article proposes a new sonification framework, Go-with-the-Flow, informed by physiotherapists and people with CP. The framework proposes articulation of user-defined sonified exercise spaces (SESs) tailored to psychological needs and physical capabilities that enhance body and movement awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 68 publications
5
105
0
Order By: Relevance
“…Request permissions from permissions@acm.org. CHI' 16 should continue (unstable) and points of resolution where the music feels concluded (stable) [1]. For example, in a pop song there may be a build in tension before the chorus, partly achieved through aspects of musical instability and which will often become resolved at the end of the chorus.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Request permissions from permissions@acm.org. CHI' 16 should continue (unstable) and points of resolution where the music feels concluded (stable) [1]. For example, in a pop song there may be a build in tension before the chorus, partly achieved through aspects of musical instability and which will often become resolved at the end of the chorus.…”
Section: Introductionmentioning
confidence: 97%
“…Sound and visual feedback for rehabilitation has been used to provide rewards as it enhances the perception of moving (self-efficacy) [16,24], enables a better control of the body with respect to trajectories/targets [25] and shifts the attention away from pain [9,16]. Typically, the achievement of targets is rewarded through changes in the sonification, e.g., the ending of sound beyond the target, dynamically changing sound (increasing tone scales) to indicate progression [25,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that introduction of new exercise tasks was successful only if small changes were made to current daily activities. Other studies advocated a shift of attention strategy [54] as well as focusing on pleasurable activities [55]. These studies suggest the strong need to base any recommendation system on the personal preferences and routine behavior of each individual.…”
Section: Strategies To Address Psychological Barriersmentioning
confidence: 99%
“…The specific test equipment is to integrate hand gesture and voice into the ARMAR II and III robotic platform to establish a natural human-computer interaction system. Researchers at the University of Dublin, including Han [9], designed speech recognition, sight recognition, and face recognition in the Lego robot platform in order to enhance the naturalness of humancomputer interaction.…”
Section: Introductionmentioning
confidence: 99%